Allergic sinusitis and severe asthma caused by occupational exposure to locust bean gum: Case report. Issue 7 (12th May 2017) - Hawley, Brie; Cummings, Kristin J.; Mohammed, Mohammed; Dimmock, Anne E.; Bascom, Rebecca
Abstract : We present a case that highlights the difficulties with diagnosis and the dangers of occupational allergic sinusitis and asthma left unrecognized. We describe the case history of a man who experienced work‐related symptoms 1 year after beginning work as a cheesemaker at a creamery, and whose respiratory symptoms progressively worsened over 16 years before an occupational cause of his asthma was identified. His initial discrete episodes of sinusitis and acute bronchitis evolved into persistent asthma of increasing severity with exacerbations requiring repeated emergency room treatment. The case described in our report emphasizes the importance of clinician diagnosis of OA, and subsequent removal from exposure, such that asthma severity does not progress to near‐fatal or fatal asthma in the sensitized worker. As demonstrated by this case report, identification of an occupational cause of asthma relies on a high degree of suspicion and excellent detective work by the clinician.